Assessment of right ventricular endocardial fibroelastosis in fetuses with critical pulmonary stenosis and pulmonary atresia with intact ventricular septum - Wang, Yue; Luo, Gang; Sun, Yi; Chen, Taotao; Pan, Silin (Frontiers in Pediatrics, 2025)
BackgroundThis study aimed to assess right ventricular (RV) endocardial fibroelastosis (EFE) in fetuses with critical pulmonary stenosis (CPS) and pulmonary atresia with intact ventricular septum (PA-IVS) and to investigate the implications of RV EFE for circulatory outcomes.MethodsFetal echocardiographic data from July 2018 to January 2021 were collected. Three reviewers independently graded EFE based on the presence and extent of endocardial echogenicity. Since this is a novel study on grading RV EFE, intra- and interobserver comparisons were performed. The associations among EFE severity, anatomic variables, and late-gestational circulatory outcomes were analysed.ResultsEighty-one patients with RV EFE were identified. By consensus, EFE severity was assessed as Grade 1 (n = 66, 81.5%) or Grade 2 (n = 15, 18.5%). At the first consultation, RV sphericity values were greater in Grade 2 EFE fetuses than in Grade 1 EFE fetuses, implying more severe noncompliance and worse diastolic function. From the first consultation to late gestation, significant differences were observed in the changes in the tricuspid/mitral valve (TV/MV) annulus diameter (P = 0.042) and TV z-score (P = 0.001) between the Grade 1 and Grade 2 RV EFE groups. Among the ten patients who underwent fetal cardiac intervention (FCI), the restoration of the TV z-score was more significant in Grade 2 RV EFE fetuses than in Grade 1 EFE fetuses. Among Grade 2 EFE cases, fetuses who underwent FCI exhibited greater changes in the right/left ventricular (RV/LV) long-axis dimension, TV/MV, and RV sphericity compared to non-FCI fetuses, indicating that FCI benefited Grade 2 EFE fetuses by restoring the development of ventricular structure.ConclusionsThis study graded RV EFE in fetuses with CPS/PA-IVS, shedding light on its implications for circulatory outcomes. FCI offered benefits in Grade 2 RV EFE patients, suggesting its potential to preserve cardiac development in affected fetuses with CPS/PA-IVS.